2009
DOI: 10.1038/ejcn.2008.64
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of portion size in children's dietary assessment: lessons learnt

Abstract: Background/Objectives: Assessing the dietary intake of young children is challenging. In any 1 day, children may have several carers responsible for providing them with their dietary requirements, and once children reach school age, traditional methods such as weighing all items consumed become impractical. As an alternative to weighed records, food portion size assessment tools are available to assist subjects in estimating the amounts of foods consumed. Existing food photographs designed for use with adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 8 publications
0
47
1
4
Order By: Relevance
“…The smallest portions of the various picture series were chosen for the youngest children much more frequently than the larger portions, indicating that the pictures series may not show the most appropriate portion sizes for children in this age group. It has been shown that children's estimates using age-appropriate photographs were more accurate than when using photographs designed for adults (Foster et al, 2006(Foster et al, , 2008(Foster et al, , 2009. In the present study, units and HHMs were used more often for quantification than the picture book, and the participants found it more difficult to use HHM than the picture book.…”
Section: Discussioncontrasting
confidence: 46%
“…The smallest portions of the various picture series were chosen for the youngest children much more frequently than the larger portions, indicating that the pictures series may not show the most appropriate portion sizes for children in this age group. It has been shown that children's estimates using age-appropriate photographs were more accurate than when using photographs designed for adults (Foster et al, 2006(Foster et al, , 2008(Foster et al, , 2009. In the present study, units and HHMs were used more often for quantification than the picture book, and the participants found it more difficult to use HHM than the picture book.…”
Section: Discussioncontrasting
confidence: 46%
“…A sua estrutura e o protocolo de aplicação permitem situar as crianças no tempo (dia de ontem), no espaço (refeições ordenadas cronologicamente) e estimular a imaginação visual (ilustração dos alimentos em cada uma das refeições), com o propósito de facilitar o processo de recuperação de informações. A imaginação visual e a familiaridade com o alimento são importantes mecanismos de recuperação de informações pela memória de curto prazo, utilizada por crianças em idade escolar 16,17,27 .…”
Section: Resultsunclassified
“…O instrumento não foi delineado para obter informações sobre freqüências e quantidades, pois essas capacidades não estão bem desenvolvidas em crianças que ainda não alcançaram o estágio de raciocínio abstrato 16,17 .…”
Section: Desenvolvimento Do Quadaunclassified
“…Knowledge of the sources of dietary fat of South African schoolchildren is a prerequisite for such a change, something not yet available on national level. Other refinements would involve portion size estimation, which remains a major challenge in dietary assessment 41 and the measurement of frequency of intake. Also the scoring system presents refinement opportunities.…”
Section: Discussionmentioning
confidence: 99%